COMIC STRIPS FOR LANGUAGE TEACHING: THE BENEFITS AND CHALLENGES ACCORDING TO RECENT RESEARCH - Eka Anastasia Wijaya; Ni Komang Arie Suwastini; Ni Luh Putu Sri Adnyani; Kadek Eva Krishna Adnyani (Universitas Islam Negeri Alauddin Makassar, 2021)
Recent studies have argued for the use of comic strips in language teaching, while concerns with the challenges in its application are also frequently highlighted. Using George’s (2008) model of literature review, the present study will elaborate on the use of comic strips as a medium of learning, its benefits, and the challenges in its implementation. The data sources are research articles related to the implementation of comic strips for language teaching, published in reputable international journals and accredited national journals from 2011 to 2020. The review reveals that previous studies have proven that comic strips in language teaching can promote students’ vocabulary, improve students' grammar competence, support the students' reading skills, and help the students who lack writing skills. However, these studies also show concerns on challenges in implementing comic strips in language teaching, such as its relevance, the choices of the topics, and how it cannot support spoken skills as much as it would support the written skills. It implies that while comic strips can be good media for teaching language, teachers should also find strategies in overcoming the challenges that may occur during its implementation.